PENGUATAN HAK PERORANGAN ATAS TANAH ULAYAT DALAM PENERBITAN SERTIFIKAT HAK MILIK BERDASARKAN PELEPASAN HAK ADAT DI KANTOR PERTANAHAN KOTA JAYAPURA - Andhis Syandyah Maswonggo (JOURNAL SAINS STUDENT RESEARCH, 2024)
The existence of customary law communities over customary land in Jayapura City is still dominated by applicable customary rules. The absence of regional regulations governing the administration and inventory of customary land registration has caused legal uncertainty which is one of the causes of land disputes in various regions in Papua. Since the enactment of the UUPA that regulates land in Indonesia, there has been a unification of land rights laws. One of the instruments for strengthening customary land rights based on the UUPA refers to the conversion provisions. Departing from these conditions, the purpose of this study is to find out and analyze the legal basis that strengthens the conversion of customary rights in the issuance of individual property rights certificates through the release of customary rights in Jayapura City. As well as knowing efforts to strengthen the conversion of land customary rights in the issuance of individual ownership certificates through the release of customary rights at the Jayapura City Land Office. The method in this study uses empirical juridical research, or called field research. The object of this research is the conversion of customary land rights in Jayapura City, the subjects in this study are the parties who will provide data or information related to the research object. Data analysis uses a qualitative approach. The result of this study is that the legal basis that strengthens the conversion of customary rights into property rights certificates based on the release of customary rights in Jayapura City is in accordance with the applicable positive law, but there is a difference in its implementation, namely the release of customary rights carried out by the customary head is transferred as an individual right, not customary land is released to the state in accordance with the applicable positive law. Efforts to strengthen the conversion of customary land rights in the issuance of individual ownership certificates through the release of customary rights if you want to ensure legal certainty of the rights to the land owned must be registered. The purpose of registering former land belonging to customary land through the release of customary rights as the basis for land ownership rights is to strengthen the right to land owned by issuing a certificate of ownership as the legal owner.